1995
DOI: 10.1007/bf01256709
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hypervascular hepatocellular carcinoma by using spiral volumetric CT: Comparison of US and MR imaging

Abstract: We suggest that the combination of precontrast SVCT and CT-ADP is an essential modality to screen for HCC in patients with chronic liver disease. CT-EP did not contribute to the detection of hypervascular HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…In previous studies, the sensitivity for HCC was 72-75% with dynamic MRI and 47-50% with spin-echo MRI (8,9,15). In the present study, the conventional MRI showed similar sensitivity while the SENSE MRI showed higher sensitivity (91.7%) compared with the previous studies.…”
Section: Discussionsupporting
confidence: 60%
“…In previous studies, the sensitivity for HCC was 72-75% with dynamic MRI and 47-50% with spin-echo MRI (8,9,15). In the present study, the conventional MRI showed similar sensitivity while the SENSE MRI showed higher sensitivity (91.7%) compared with the previous studies.…”
Section: Discussionsupporting
confidence: 60%
“…13,14,38 Tumor vascularity is usually high in HCC compared to other liver tumors. 39,40 We speculate that hypovascular HCCs are difficult to PCNA, proliferating cell nuclear antigen * P Ͻ 0.01; ** P Ͻ 0.05 a Mean value of microvessel count detect by conventional imaging and to treat by chemoembolization or other therapy, and that treatment selection is therefore limited. In patients in whom repeated hepatectomy is impossible, survival in those patients with hypovascular HCC would be poorer after recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…We have been following a large number of patients with chronic viral liver disease at regular intervals for early detection. After the installment of the helical computed tomography (CT) combined with angiography system in 2000, we have been carrying out helical CT angiography, namely CT arterial portography (CTAP) and CT hepatic arteriography (CTHA), whenever suspicion of HCC arises in patients; it is well established that helical CT angiography is highly diagnostic for hypervascular HCC 8,9 . We have so far found small HCC less than 2 cm in diameter in 29 patients.…”
Section: Introductionmentioning
confidence: 99%